2007
DOI: 10.1136/bjsm.2007.038778
|View full text |Cite
|
Sign up to set email alerts
|

Changes in technical regulations and drivers’ safety in top-class motor sports

Abstract: Motor racing is a dangerous sport and an inherently risky activity. The organisers of top-class motor sports championships, Formula One and MotoGP, have agreed on a set of regulations to reduce speed and improve safety over the last 10 years. These changes include limitations in weight, fuel and engine capacity. Nevertheless, there is evidence that most of the restrictions that have been introduced over the past 10 years have failed slow down vehicles, since the lap times have decreased almost linearly from 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
1
4
0
1
Order By: Relevance
“…In the SCH group, there was a poor correlation between Free T 3 and Free T 4 with creatinine and eGFR [Table 5]. An inverse association between TSH levels and eGFR in OHT group was also found in studies in Italy (n = 9888), 20 Norway (n = 29 480) 21 and Korea (n = 2284) 22 which are similar findings with our study. Woodward A. et al 23 concluded that eGFR of the hypothyroid, euthyroid patients were 64 mL/min/1.73 m 2 and 77 mL/min/1.73 m 2 respectively.…”
Section: Discussionsupporting
confidence: 89%
“…In the SCH group, there was a poor correlation between Free T 3 and Free T 4 with creatinine and eGFR [Table 5]. An inverse association between TSH levels and eGFR in OHT group was also found in studies in Italy (n = 9888), 20 Norway (n = 29 480) 21 and Korea (n = 2284) 22 which are similar findings with our study. Woodward A. et al 23 concluded that eGFR of the hypothyroid, euthyroid patients were 64 mL/min/1.73 m 2 and 77 mL/min/1.73 m 2 respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The results show that during driving the kart drivers experienced an average acceleration of about 0.7 G , and a maximum acceleration of about 2.4 G . This compares with a F1 car, which can achieve a lateral acceleration of about 4.5 G on cornering, while a high‐performance road car is said to achieve a maximum of 1 G (Lippi, Salvagno, Franchini, & Guidi, 2007; Watkins, 2006). Although the G values during kart driving are approximately half those during F1 driving, it could be considered that the physical load during motor sports can be quite high.…”
Section: Discussionmentioning
confidence: 99%
“…The 125-cc class uses a 2-stroke engine while Moto2 and MotoGP use 4-stroke engines. Although road-race motorcycling performance depends on the characteristics of the motorcycle as well as on the capabilities of the riders, research has focused mainly on the technology advances of the motorbikes and riding equipment [8,23] , pattern of injuries [16,28,29] , and safety [20,21] . At the present, there are few scientifi c data on the physical and physiological load in training and competition [2,6,7,10,13] , and there is no information on the anthropometric and physical characteristics of road-race motorcyclists.…”
Section: Introduction ▼mentioning
confidence: 99%